Excess child mortality after discharge from hospital in Kilifi, Kenya: a retrospective cohort analysis - Jennifer C Moïsi; Hellen Gatakaa; James A Berkley; Kathryn Maitland; Neema Mturi; Charles R Newton; Patricia Njuguna; James Nokes; John Ojal; Evasius Bauni; Benjamin Tsofa; Norbert Peshu; et al. (Bulletin of the World Health Organization)
OBJECTIVE: To explore excess paediatric mortality after discharge from Kilifi District Hospital, Kenya, and its duration and risk factors. METHODS: Hospital and demographic data were used to describe post-discharge mortality and survival probability in children aged < 15 years, by age group and clinical syndrome. Cox regression models were developed to identify risk factors. FINDINGS: In 2004-2008, approximately 111 000 children were followed for 555 000 person-years. We analysed 14 971 discharges and 535 deaths occurring within 365 days of discharge. Mortality was higher in the post-discharge cohort than in the community cohort (age-adjusted rate ratio, RR:7.7; 95% confidence interval, CI: 6.6-8.9) and declined little over time.An increased post-discharge mortality hazard was found in children aged < 5 years with the following: weight-for-age Z score <-4 (hazard ratio, HR:6.5); weight-for-age Z score >-4 but <-3 (HR:3.4); hypoxia (HR:2.3); bacteraemia (HR:1.8); hepatomegaly (HR:2.3); jaundice (HR:1.8); hospital stay >13 days (HR:1.8).Older age was protective (reference <1 month): 6-23 months, HR:0.8; 2-4 years, HR:0.6. Children with at least one risk factor accounted for 545 (33%) of the 1655 annual discharges and for 39 (47%) of the 83 discharge-associated deaths. CONCLUSION: Hospital admission selects vulnerable children with a sustained increased risk of dying. The risk factors identified provide an empiric basis for effective outpatient follow-up.